Majalah Cilukba: Islam, Tradisi Lokal dan Rekonstruksi Kebangsaan - Okta Nurul Hidayati (Academica: Journal of Multidisciplinary Studies, 2018)
AbstractThe media has a big role in conveying information, even able to reconstruct an insight of Islam and nationality. In this study, the author argues that Cilukba magazine, as a representation of Islam, helped reconstruct the values of Indonesian nationality among children. The area of reconstruction in this paper focuses on several subjects: language, games and traditional food. Furthermore, this paper would like to analyze how Cilukba magazine represents national values. This paper is useful to see the authority of popular print media in constructing the face of Islamic nationalism in Indonesia. This research is a type of qualitative research with content analysis techniques. This research uses written data sources, where the primary data sources used are the Cilukba and Cilukba Junior magazines, while the secondary data sources come from junals and books. The result, it is known that Cilukba magazine, contributes towards strengthening national values through local culture. Strengthening local culture is manifested in the form of languages, games and traditional foods, which are represented in magazine rubrics. With that being seen, first, Cilukba magazine raised the locality of culture to knit nationality. Second, Islam can contribute to national values and accommodate culture in IndonesiaKeywords: Cilukba magazine, Islam, nationality value